2017
DOI: 10.1371/journal.pcbi.1005650
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacies of moxifloxacin, levofloxacin and gatifloxacin in tuberculosis granulomas using a multi-scale systems pharmacology approach

Abstract: Granulomas are complex lung lesions that are the hallmark of tuberculosis (TB). Understanding antibiotic dynamics within lung granulomas will be vital to improving and shortening the long course of TB treatment. Three fluoroquinolones (FQs) are commonly prescribed as part of multi-drug resistant TB therapy: moxifloxacin (MXF), levofloxacin (LVX) or gatifloxacin (GFX). To date, insufficient data are available to support selection of one FQ over another, or to show that these drugs are clinically equivalent. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 69 publications
0
61
0
1
Order By: Relevance
“…In an effort to characterize how caseum affects antibiotic distribution, there have been a number of studies that image the distribution of antibiotics in granulomas and quantify antibiotic molecular binding to caseum . Pienaar et al have utilized MALDI‐MS images and experimentally determined temporal granuloma antibiotic concentration measurements to compare efficacy of tuberculosis therapy with 3 different fluoroquinolones: moxifloxacin, levofloxacin, and gatifloxacin. The 3 fluoroquinolones display different distribution patterns in granulomas that GranSim can recapitulate.…”
Section: Modulating the Dynamic Inflammatory Balance For Tb Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to characterize how caseum affects antibiotic distribution, there have been a number of studies that image the distribution of antibiotics in granulomas and quantify antibiotic molecular binding to caseum . Pienaar et al have utilized MALDI‐MS images and experimentally determined temporal granuloma antibiotic concentration measurements to compare efficacy of tuberculosis therapy with 3 different fluoroquinolones: moxifloxacin, levofloxacin, and gatifloxacin. The 3 fluoroquinolones display different distribution patterns in granulomas that GranSim can recapitulate.…”
Section: Modulating the Dynamic Inflammatory Balance For Tb Therapymentioning
confidence: 99%
“…In an effort to characterize how caseum affects antibiotic distribution, there have been a number of studies that image the distribution of antibiotics in granulomas and quantify antibiotic molecular binding to caseum. 130,132,133 Pienaar et al 134 Because active TB can be considered an immune response that is out of balance-too little pro-inflammatory mediators, or too many anti-inflammatory mediators, another approach to treatment is to modify the levels of 1 or both of the pro-and anti-inflammatory responses to achieve latency. The same idea could also be considered for clinically latent TB, though the idea would be to tip the distribution slightly toward pro-inflammatory responses and thus eliminate Mtb without inducing additional inflammation.…”
Section: Modul Ating the Dynamic Infl Ammatory Bal An Ce For Tb Thementioning
confidence: 99%
“…(3-7). Meanwhile, biological factors not explored in this study, such as antibiotic type and 330 concentration (10-13, 46, 47), pharmacodynamic and pharmacokinetic features (58,59), and the 331 selective pressure of the host immune system (60), may also influence the evolution of FQ-R. 332…”
Section: Mutational Profile For Fluoroquinolone-resistance In Vitro Rmentioning
confidence: 99%
“…Therefore, the PK profile in these regions is likely to be different from that measured in plasma. A reasonable PK/PD modelling approach in such cases is to use a hypothetical “effect compartment” (30,31) mimicking the concentration at the site of action which, while dependent on the concentration in plasma, is “delayed” by the drug traversing through the numerous layers of biological tissue, thus significantly smoothing out peak and trough concentrations. Also, the time over a certain concentration would be very different in this effect compartment.…”
Section: Figurementioning
confidence: 99%
“…Fortunately, the last decade has seen considerable efforts toward developing accurate methods (Table 1) to measure drug levels directly in Mtb-infected tissues (27)(28)(29). Through the application of advanced chromatographic, mass spectrometry, and imaging techniques including HPLC coupled to tandem mass spectrometry (LC-MS/MS) and MALDI mass spectrometry imaging (MALDI-MSI), the quantification of tissue and lesion distribution of known and experimental anti-TB drugs in animal models and clinical samples has become increasingly attainableprimarily through the work of Veronique Dartois and colleagues (4,7,8,28,54) -thus offering the prospect of informing a systems pharmacology approach to the design of antimycobacterial therapy (55). In addition to the well-established appreciation that TB drugs can be differentially active against bacilli in different metabolic states (56)(57)(58), these new analytical techniques have demonstrated that those same drugs can also possess distinct lesion-penetrating abilities (6,7,9,18).…”
Section: Introductionmentioning
confidence: 99%